KERUSAKAN TEGANGAN TINGGAL AKIBAT PENYARADAN DENGAN TRAKTOR PADA BERBAGAI TINGKAT KERAPATAN TEGAKAN - Dulsalam Dulsalam; Sukanda Sukanda; Ishak Sumantri (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
An investigation on residual stand damages caused by skidding tractor on several stand density levels was carried out at PT Sumpol Timber in South Kalimantan in 1987. Forty five sample plots were selected randomly in this research. The purpose is to gather information about the resdiual stand damages caused by skidding tractor on several stand density levels. The result of investigation reveals that : 1. The number of trees having diameter of 20 cm and up varies from 80 to 300 trees/ha with an average of 190.22 trees/ha. 2. The residual stand damages for the area with stand densities ot < 150, 150 -199, and > 200 trees/ha were 16, 7, 28.3,and 39. 0 trees/ha, respectively. They are significantly different.3. It is suggested that the skidding operations, especially in high stand density levels, be done with better planning in-order to save powers, costs and resources.